High-temperature-resistant lithium iron phosphate power battery and preparation process thereof

By using carbon-coated lithium iron phosphate and artificial graphite as battery materials, combined with specific binders and conductive agents, the problems of low cycling performance and unstable charge and discharge at high temperatures are solved, and higher stability and longer cycle life are achieved.

CN119560619AInactive Publication Date: 2025-03-04BSL NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411811704.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Lithium iron phosphate batteries have low cycling performance at high temperatures, unstable charging and discharge, and are prone to problems of bulging and liquid leakage.

Method used

Carbon-coated lithium iron phosphate is used as the positive electrode material, artificial graphite is used as the negative electrode material, specific binders and conductive agents are used, carbon-coated aluminum foil is combined as the current collector, and the performance of the separator is improved through ceramic coating.

Benefits of technology

It improves the stability and circulation life of lithium iron phosphate batteries at high temperatures, and reduces the problems of bulging and liquid leakage caused by unstable charge and discharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005180706510000051
    Figure BDA0005180706510000051
  • Figure BDA0005180706510000061
    Figure BDA0005180706510000061
  • Figure BDA0005180706510000071
    Figure BDA0005180706510000071
Patent Text Reader

Abstract

The invention relates to the field of power batteries, and discloses a high-temperature-resistant lithium iron phosphate power battery and a preparation process thereof. The high-temperature-resistant lithium iron phosphate power battery comprises a positive plate, a diaphragm, a negative plate, electrolyte and a shell, wherein the positive plate comprises a positive current collector and a coated positive material; the negative plate is composed of a negative current collector and a coated negative material; the positive electrode material is prepared from carbon-coated lithium iron phosphate, a conductive agent and a binder according to a weight ratio of 100: (4-6): (50-60), and the negative electrode material is prepared from artificial graphite, a conductive agent and a binder according to a weight ratio of 100: (2-4): (60-70); the binder is prepared from the following raw materials in percentage by weight: 20-30% of carboxylated styrene-butadiene emulsion, 10-15% of polytetrafluoroethylene emulsion, 10-12% of dispersing agent, 2-4% of hydroxyethyl cellulose and the balance of water. And the prepared lithium iron phosphate power battery has good high-temperature-resistant stability and cycle period, and the problem of swelling is not easy to occur.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of power batteries, and in particular to a high-temperature resistant lithium iron phosphate power battery and a preparation process thereof. Background Art

[0002] Lithium iron phosphate battery is a battery that uses lithium iron phosphate (LiFePO 4 ) as the positive electrode material and carbon as the negative electrode material. During the charging process, some lithium ions in lithium iron phosphate escape from the negative electrode, are transferred to the negative electrode through the electrolyte, and are embedded in the negative electrode carbon material; at the same time, electrons are released from the positive electrode and reach the negative electrode from the external circuit to maintain the balance of the chemical reaction. During the discharge process, lithium ions escape from the negative electrode and reach the positive electrode through the electrolyte. At the same time, the negative electrode releases electrons and reaches the positive electrode from the external circuit to provide energy to the outside world. Lithium iron phosphate batteries have the advantages of high operating voltage, low self-discharge rate, and no memory effect.

[0003] When lithium iron phosphate batteries are used in transportation vehicles, such as electric vehicles, the lithium iron phosphate batteries will continue to discharge during the long-term operation of the electric vehicles, and the temperature of the lithium iron phosphate batteries will continue to rise, and the high temperature can reach 60-70°C. Long-term high temperature can easily reduce the cycle performance of the lithium iron phosphate battery; at the same time, it also makes the charging and discharging of the lithium iron phosphate battery unstable, which in turn causes battery bulging and even electrolyte leakage, reducing the performance of the lithium iron phosphate battery. Summary of the invention

[0004] In order to solve the problems of low cycle performance of existing lithium iron phosphate batteries at high temperatures and unstable charging and discharging which makes the batteries prone to bulging and leakage, the present application provides a high temperature resistant lithium iron phosphate power battery and a preparation process thereof.

[0005] In a first aspect, the present application provides a high temperature resistant lithium iron phosphate power battery, which adopts the following technical scheme: a high temperature resistant lithium iron phosphate power battery, comprising a positive electrode sheet, a separator, a negative electrode sheet, an electrolyte and a shell, wherein the positive electrode sheet comprises a positive electrode collector and a positive electrode material coated on the positive electrode collector, wherein the positive electrode collector is a carbon-coated aluminum foil; the separator is a coated separator, wherein the substrate of the separator is polypropylene, and the coating of the separator is ceramic; the negative electrode sheet comprises a negative electrode collector and a negative electrode material coated on the negative electrode collector, wherein the negative electrode collector is a carbon-coated aluminum foil; the positive electrode material is made of carbon-coated lithium iron phosphate, a conductive agent and a binder in a weight ratio of 100:(4-6):(50-60), and the negative electrode material is made of artificial graphite, a conductive agent and a binder in a weight ratio of 100:(2-4):(60-70); the binder is made of the following raw materials in weight percentage: Carboxylated styrene butadiene emulsion 20-30% Polytetrafluoroethylene emulsion 10-15% Dispersant 10-12% Hydroxyethylcellulose 2-4% Water balance.

[0006] By adopting the above technical scheme, carbon-coated lithium iron phosphate is used as the active material of the positive electrode material, and is compounded with a conductive agent and an adhesive to obtain a positive electrode material, and the positive electrode material can be stably bonded to the positive electrode collector; artificial graphite is used as the active material of the negative electrode material, and is compounded with a conductive agent and an adhesive, so that the negative electrode material can be stably bonded to the negative electrode collector; polypropylene is used as the body of the diaphragm and coated with a ceramic coating, which improves the liquid absorption rate and biaxial stretching and shrinkage of the diaphragm, and ensures the liquid storage rate of the electrolyte in a high temperature environment; an adhesive made of carboxylated butadiene styrene emulsion, polytetrafluoroethylene emulsion, dispersant, hydroxyethyl cellulose and water is used in the positive and negative electrode materials. The binder not only improves the dispersion uniformity and bonding stability of the active material, but also improves the adhesion between the active material and the current collector, ensures the structural stability of the positive and negative electrodes, is beneficial to the formation of the SEI film, and prevents the excessive dissolution of the positive and negative electrodes during charging and discharging, thereby improving the stability and cycle life of the lithium iron phosphate power battery at high temperatures, and reducing the bulging and leakage problems of the lithium iron phosphate power battery caused by unstable charging and discharging; compared with traditional adhesive materials such as polyvinyl alcohol, polytetrafluoroethylene, polyolefins, polyvinylidene fluoride, etc., it is not easily affected by the immersion and swelling of the electrolyte in a high temperature environment.

[0007] Preferably, the dispersant is composed of hydroxyethyl chitosan and 2-acrylamide-2-methylpropane sulfonic acid in a weight ratio of 1:(2-3).

[0008] By adopting the above technical scheme, hydroxyethyl chitosan and 2-acrylamide-2-methylpropane sulfonic acid in a relatively optimal weight ratio are used as dispersants, which can be interwoven with carboxylated styrene butadiene emulsion, polytetrafluoroethylene emulsion and hydroxyethyl cellulose to form a network structure, thereby improving the dispersion uniformity of carbon-coated lithium iron phosphate and artificial graphite, while improving the uniformity and adhesion of positive and negative electrode materials; thereby improving the structural stability of the positive and negative electrode sheets, and improving the high temperature stability and cycle performance of the prepared lithium iron phosphate power battery.

[0009] Preferably, the adhesive is prepared by the following steps: adding hydroxyethyl cellulose and a dispersant into water, adding carboxylated styrene butadiene emulsion and polytetrafluoroethylene emulsion after dissolving, heating to 85-95° C., reacting for 1-2 hours, and preparing the adhesive.

[0010] By adopting the above technical solution, under the optimal time and temperature conditions, carboxylated styrene butadiene emulsion, polytetrafluoroethylene emulsion, hydroxyethyl cellulose and dispersant are interwoven to form an adhesive with a network structure, which can effectively improve the bonding strength of the positive electrode material and the negative electrode material, ensure the stable bonding between the active materials under high temperature environment, thereby avoiding the shedding or separation of the active materials caused by high temperature. At the same time, the adhesive can also promote the formation of the SEI film, making it more dense and stable, further improving the cycle performance and safety of the battery under high temperature conditions.

[0011] Preferably, the conductive agents of the positive electrode material and the negative electrode material are both composed of conductive carbon black and carbon nanotubes in a weight ratio of (3-4):1.

[0012] By adopting the above technical solution, conductive carbon black and carbon nanotubes with a better weight ratio can be used as conductive agents for positive and negative electrode materials and dispersed into the positive and negative electrode materials, significantly improving the conductive properties of the positive and negative electrode sheets.

[0013] Preferably, the carbon-coated aluminum foil has an aluminum foil thickness of 10-20 μm, and a carbon coating thickness of 0.5-2 μm.

[0014] By adopting the above technical solution, the carbon-coated aluminum foil with better specifications improves the conductivity and mechanical stability of the positive electrode collector and enhances the overall performance of the battery.

[0015] Preferably, the carbon content of the carbon-coated lithium iron phosphate is 1.5±0.2%.

[0016] By adopting the above technical solution and controlling the optimal carbon content, it is possible to effectively improve the ion conductivity while preventing the lithium iron phosphate metal and the electrolyte from contacting at high temperatures and avoiding metal dissolution, thereby improving the high temperature stability of the battery and extending the cycle life of the battery.

[0017] Preferably, the electrolyte is prepared from the following raw materials in weight percentage: 30-35% of ethylene carbonate, 27.5-30% of ethyl methyl carbonate, 5-10% of propylene carbonate, 25-30% of diethyl carbonate and 2.5-5% of vinylene carbonate.

[0018] By adopting the above technical scheme, ethylene carbonate, ethyl methyl carbonate, propylene carbonate, diethyl carbonate and vinylene carbonate in a preferred weight ratio are used as the electrolyte. The electrolyte has good stability and a good electrolyte storage rate in a high temperature environment, thereby reducing the problem of performance degradation caused by electrolyte evaporation.

[0019] Preferably, the coating has a thickness of 5-8 μm.

[0020] By adopting the above technical solution, the coating with optimal thickness increases the mechanical strength and thermal stability of the diaphragm, ensuring that the diaphragm is not easily deformed or shrunk in a high temperature environment, thereby improving the safety and reliability of the battery.

[0021] In a second aspect, the present application provides a preparation process for a high temperature resistant lithium iron phosphate power battery, which adopts the following technical solution: A preparation process of a high temperature resistant lithium iron phosphate power battery comprises the following steps: The carbon-coated lithium iron phosphate, the conductive agent and the binder are mixed and dispersed to obtain a positive electrode material, the positive electrode material is coated on a positive electrode current collector, dried, and cut to obtain a positive electrode sheet; Mixing and dispersing artificial graphite, a conductive agent and a binder to obtain a negative electrode material, coating the negative electrode material on a negative electrode current collector, drying, and cutting to obtain a negative electrode sheet; The positive electrode sheet, the separator and the negative electrode sheet are stacked to obtain a battery cell; The battery cell is assembled into a shell, and the electrolyte is injected. The battery cell is then left to stand at a temperature of 45-50°C and subjected to vacuum forming. After vacuum forming, the battery cell is aged and divided into different capacities at a temperature of 45-50°C to obtain a lithium iron phosphate power battery.

[0022] By adopting the above technical solution, positive and negative electrode sheets are prepared, and the positive and negative electrode sheets and separators are stacked to form battery cells. The battery cells are then assembled into a shell and injected with electrolyte. The cells are allowed to stand at an optimal temperature and are vacuum formed to allow the electrolyte to be evenly infiltrated and remove impurities and moisture, thereby improving the quality and stability of the lithium iron phosphate battery.

[0023] Preferably, in the cell manufacturing step, a Z-shaped lamination process is used for lamination, and the vacuum degree of the vacuum is -0.05 to -0.1 KPa.

[0024] By adopting the above technical solutions, the Z-shaped lamination process can effectively improve the internal space utilization of the battery cell, ensure close contact between the layers, reduce the internal resistance of the battery cell, and improve the overall performance of the battery. The vacuum degree during the vacuum formation process is controlled within the range of -0.05 to -0.1KPa, which helps to completely remove moisture and gas from the battery cell and enhance the high temperature adaptability and stability of the battery.

[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. The high temperature resistant lithium iron phosphate power battery of the present application uses carbon-coated aluminum foil as the positive electrode current collector and the negative electrode current collector, uses carbon-coated lithium iron phosphate as the positive electrode active material, and is compounded with a conductive agent and a binder as the positive electrode material, and uses artificial graphite as the negative electrode active material, and is compounded with a conductive agent and a binder as the negative electrode material. The binder is made of carboxylated butadiene styrene emulsion, polytetrafluoroethylene emulsion, dispersant, hydroxyethyl cellulose and water, which not only improves the dispersion uniformity and bonding stability of the active material, but also improves the adhesion between the active material and the current collector, ensures the structural stability of the positive and negative electrode sheets, is conducive to the formation of SEI film, and prevents the problem of excessive dissolution of the positive and negative electrode sheets during charging and discharging, thereby improving the stability and cycle life of the prepared lithium iron phosphate power battery at high temperature, and reducing the bulging and leakage problems of the lithium iron phosphate power battery caused by unstable charging and discharging.

[0026] 2. Using hydroxyethyl chitosan and 2-acrylamide-2-methylpropane sulfonic acid in a preferred weight ratio as dispersants, it can be interwoven with carboxylated styrene butadiene emulsion, polytetrafluoroethylene emulsion and hydroxyethyl cellulose to form a network structure, thereby improving the dispersion uniformity of carbon-coated lithium iron phosphate and artificial graphite, while improving the uniformity and adhesion of positive and negative electrode materials; thereby improving the structural stability of the positive and negative electrode sheets, and improving the high temperature stability and cycle performance of the prepared lithium iron phosphate power battery.

[0027] 3. The quality and stability of the prepared lithium iron phosphate battery are improved through the preparation process of the present application. DETAILED DESCRIPTION

[0028] The present application is further described in detail below with reference to the embodiments.

[0029] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used: 1. Carbon-coated aluminum foil: Kejing brand, aluminum foil thickness is 10-20μm, carbon-coated thickness is 0.5-2μm.

[0030] 2. Carbon-coated lithium iron phosphate: Kejing brand, model P198-S20, carbon content is 1.3-1.7%; 3. Artificial graphite: CLUDE brand, graphitization degree 92-95%, particle size D10 is 8.5±2μm, D50 is 13.5±2μm, D90 is 21±3μm.

[0031] 4. Carboxylated styrene butadiene emulsion: Mingxiang Chemical, model MX613, solid content 50%; 5. Polytetrafluoroethylene emulsion: Japan Daikin, model D-210C; 6. Hydroxyethyl chitosan: KM, deacetylation degree 85%; 7. 2-Acrylamide-2-methylpropanesulfonic acid: Xing Yan, CAS No. 15214-89-8; 8. Conductive carbon black: Liyou brand, TOB-C45; 9. Carbon nanotubes: LG Chem, model BT1001M.

[0032] Preparation example of adhesive Preparation Example 1 Preparation Example 1 discloses an adhesive, which is prepared by the following steps: 0.2 kg of hydroxyethyl cellulose and 1.2 kg of vinyl trimethoxy silane were added as dispersants into 5.1 kg of water, and after dissolution, 2 kg of carboxylated styrene butadiene emulsion and 1.5 kg of polytetrafluoroethylene emulsion were added, the temperature was raised to 85° C., and the reaction was carried out for 2 hours to obtain an adhesive.

[0033] Preparation Example 2-3 The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 1 below for details.

[0034] Table 1 Parameters of Preparation Examples 1-3 Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the dispersant is different. The dispersant in Preparation Example 4 is composed of 0.4 kg hydroxyethyl chitosan and 0.8 kg 2-acrylamide-2-methylpropane sulfonic acid, and the rest is the same as Preparation Example 1.

[0035] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that the dispersant consists of 0.3 kg hydroxyethyl chitosan and 0.9 kg 2-acrylamide-2-methylpropane sulfonic acid, and the rest is the same as Preparation Example 1.

[0036] Preparation Comparative Example 1 The difference between Preparation Example Comparative Example 1 and Preparation Example 1 is that an equal amount of carboxylated styrene butadiene emulsion is replaced by styrene butadiene emulsion, and the rest is the same as Preparation Example 1.

[0037] Preparation Comparative Example 2 The difference between Preparation Comparative Example 2 and Preparation Example 1 is that the amount of dispersant used is 0.5 kg, the amount of water used is 5.6 kg, and the rest is the same as Preparation Example 1.

[0038] Preparation example of electrolyte Preparation Example 6 Preparation Example 6 discloses an electrolyte, which is prepared by the following steps: 3 kg of ethylene carbonate, 3 kg of ethyl methyl carbonate, 0.5 kg of propylene carbonate, 3 kg of diethyl carbonate and 0.5 kg of vinylene carbonate are mixed uniformly to prepare an electrolyte.

[0039] Preparation Example 7-8 The difference between Preparation Example 7-8 and Preparation Example 6 is that the amounts of raw materials used are different, see Table 2 below for details.

[0040] Table 2 Parameters of Preparation Examples 6-8 Example

[0041] Example 1 Example 1 discloses a high temperature resistant lithium iron phosphate power battery, comprising a positive electrode sheet, a separator, a negative electrode sheet, an electrolyte and a shell. The positive electrode sheet includes a positive electrode collector and a positive electrode material coated on the current collector. The positive electrode collector is a carbon-coated aluminum foil, the thickness of the carbon-coated aluminum foil is 20 μm, and the carbon coating thickness is 2 μm. The positive electrode material is made of carbon-coated lithium iron phosphate, a conductive agent and an adhesive. The carbon content of the carbon-coated lithium iron phosphate is 1.5%. The thickness of the positive electrode material is 10 μm. The diaphragm is a coated diaphragm. The substrate of the diaphragm is polypropylene, the thickness of the polypropylene is 15 μm, and the coating is ceramic, and the thickness of the coating is 5 μm. The negative electrode sheet includes a negative electrode collector and a negative electrode material coated on the negative electrode collector. The thickness of the negative electrode material is 10 μm. The negative electrode collector is also a carbon-coated aluminum foil, and the negative electrode material is made of artificial graphite, a conductive agent and an adhesive. The shell is an aluminum shell, and the inner surface of the shell is coated with a thermally conductive silicone layer. The thickness of the thermally conductive silicone layer is 0.2 μm, and the thermal conductivity of the thermally conductive silicone is 2 W / (m·K).

[0042] The high temperature resistant lithium iron phosphate power battery is prepared by the following steps: 10 kg of carbon-coated lithium iron phosphate, 0.4 kg of a conductive agent (composed of conductive carbon black and carbon nanotubes in a weight ratio of 3:1) and 6 kg of the adhesive prepared in Preparation Example 1 were mixed and dispersed, and the mixing and dispersing rate was controlled to be 1500 r / min for 30 min to prepare a positive electrode material, and the positive electrode material was coated on a positive electrode current collector, dried at a temperature of 100° C., and cut to obtain a positive electrode sheet; 10 kg of artificial graphite, 0.2 kg of a conductive agent (composed of conductive carbon black and carbon nanotubes in a weight ratio of 3:1) and 6 kg of the binder prepared in Preparation Example 1 were mixed and dispersed, and the mixing and dispersing rate was controlled to be 1500 r / min for 30 min to prepare a negative electrode material, and the negative electrode material was coated on a negative electrode current collector, dried at a temperature of 100° C., and cut to obtain a negative electrode sheet; The positive electrode sheet, the separator and the negative electrode sheet are stacked using a Z-shaped stacking machine to obtain a battery cell; The battery cell was assembled into a shell, and the electrolyte prepared in Preparation Example 6 was injected. The battery cell was then allowed to stand at 45°C for 36 hours, and then vacuum-formed at a vacuum degree of -0.05 KPa. After vacuum-formed, the battery cell was aged at 50°C for 72 hours, and then the battery cell was divided to obtain a lithium iron phosphate power battery.

[0043] Example 2-3 The difference between Example 2-3 and Example 1 is that the process parameters are different, see Table 3 below for details.

[0044] Table 3 Parameters of Examples 1-3 Example 4 The difference between Example 4 and Example 1 is that the binder of the positive electrode material and the negative electrode material in Example 4 are both from Preparation Example 4. The rest is the same as Example 1.

[0045] Example 5 The difference between Example 5 and Example 1 is that the binders of the positive electrode material and the negative electrode material in Example 5 are both from Preparation Example 5, and the rest is the same as Example 1.

[0046] Example 6 The difference between Example 6 and Example 1 is that the binder of the positive electrode material in Example 6 comes from Preparation Example 5, and the rest is the same as Example 1.

[0047] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the binders of the positive electrode material and the negative electrode material in Comparative Example 1 are both derived from the preparation of Comparative Example 1, and the rest is the same as Example 1.

[0048] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the binders of the positive electrode material and the negative electrode material in Comparative Example 2 are both derived from the preparation of Comparative Example 2, and the rest is the same as Example 1.

[0049] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the binders of the positive electrode material and the negative electrode material in Comparative Example 3 are both composed of 30 wt % of polyvinylidene fluoride and 70 wt % of N-methylpyrrolidone, and the polyvinylidene fluoride is French Arkema 2850WR; the rest is the same as Example 1.

[0050] Performance Test The following performance tests were conducted on the lithium iron phosphate power batteries prepared in Examples 1-6 and Comparative Examples 1-3: Under the test condition of 65℃, charge to 3.6V with 1C constant current, then charge to 0.05C with constant voltage, then discharge to 2.0V with 1C constant current, cycle charge and discharge, calculate the capacity retention rate of lithium iron phosphate battery after 500 cycles and 3000 cycles at 65℃. Capacity retention rate (%) = discharge capacity after cycle test / discharge capacity of initial cycle × 100%.

[0051] The following are the performance test data of the lithium iron phosphate power batteries prepared in Examples 1-6 and Comparative Examples 1-3, see Table 4 below.

[0052] Table 4 Data table of lithium iron phosphate power batteries of Examples 1-6 and Comparative Examples 1-3 The analysis is as follows: Compared with Example 1, Example 6 optimizes the ratio of the binder of the positive electrode material, and the capacity retention rate of the prepared lithium iron phosphate power battery is increased by 1% after 500 times of 65°C high temperature test, and the capacity retention rate is increased by 1.5% after 3000 times of 65°C high temperature test; and compared with Example 1, Examples 4-5 simultaneously optimize the ratio of the binder of the positive electrode material and the negative electrode material, and the capacity retention rate of the prepared lithium iron phosphate power battery is increased by 3.5% after 500 times of 65°C high temperature test, and the capacity retention rate is increased by 5% after 3000 times of 65°C high temperature test.

[0053] Compared with Example 1, in Comparative Example 1, the carboxyl styrene butadiene emulsion is replaced with styrene butadiene emulsion in equal amounts. After the obtained lithium iron phosphate power battery is tested at 65°C for 500 times, the capacity retention rate is reduced by 4%, and after the 65°C high temperature test for 3000 times, the capacity retention rate is reduced by 5%, indicating that the carboxyl styrene butadiene emulsion has a good synergistic effect with the system of the present application, and can improve the dispersibility and bonding stability of the obtained adhesive, thereby improving the high temperature cycle stability of the obtained lithium iron phosphate power battery; Compared with Example 1, in Comparative Example 2, the amount of dispersant is reduced, and the high temperature cycle performance of the obtained acid lithium iron phosphate power battery is reduced; Compared with Example 1, Comparative Example 3 uses a traditional adhesive made of polyvinylidene fluoride and N-methylpyrrolidone. Although the capacity retention rate in 500 cycles is good, reaching 91%, after 3000 tests, the capacity retention rate drops to 76%. This may be because under long-term high-temperature cycles, the positive electrode material has a dissolution problem, which reduces the high-temperature stability of the lithium iron phosphate power battery.

[0054] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high temperature resistant lithium iron phosphate power battery, comprising a positive electrode sheet, a diaphragm, a negative electrode sheet, an electrolyte and a shell, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode material coated on the positive electrode current collector, wherein the positive electrode current collector is a carbon-coated aluminum foil; the separator is a coated separator, wherein the substrate of the separator is polypropylene and the coating of the separator is ceramic; the negative electrode sheet comprises a negative electrode current collector and a negative electrode material coated on the negative electrode current collector, wherein the negative electrode current collector is a carbon-coated aluminum foil; the positive electrode material is made of carbon-coated lithium iron phosphate, a conductive agent and a binder in a weight ratio of 100:(4-6):(50-60), and the negative electrode material is made of artificial graphite, a conductive agent and a binder in a weight ratio of 100:(2-4):(60-70); the binder is made of the following raw materials in weight percentage: Carboxylated styrene butadiene emulsion 20-30% Polytetrafluoroethylene emulsion 10-15% Dispersant 10-12% Hydroxyethyl cellulose 2-4% Water balance.

2. A high temperature resistant lithium iron phosphate power battery according to claim 1, characterized in that: The dispersant consists of hydroxyethyl chitosan and 2-acrylamide-2-methylpropane sulfonic acid in a weight ratio of 1:(2-3).

3. A high temperature resistant lithium iron phosphate power battery according to claim 1, characterized in that: The adhesive is prepared by the following steps: adding hydroxyethyl cellulose and a dispersant into water, adding carboxylated styrene butadiene emulsion and polytetrafluoroethylene emulsion after dissolving, heating to 85-95° C., reacting for 1-2 hours, and preparing the adhesive.

4. A high temperature resistant lithium iron phosphate power battery according to claim 1, characterized in that: The conductive agents of the positive electrode material and the negative electrode material are both composed of conductive carbon black and carbon nanotubes in a weight ratio of (3-4):

1.

5. A high temperature resistant lithium iron phosphate power battery according to claim 1, characterized in that: The aluminum foil thickness of the carbon-coated aluminum foil is 10-20 μm, and the carbon coating thickness is 0.5-2 μm.

6. A high temperature resistant lithium iron phosphate power battery according to claim 1, characterized in that: The carbon content of the carbon-coated lithium iron phosphate is 1.5±0.2%.

7. A high temperature resistant lithium iron phosphate power battery according to claim 1, characterized in that: The electrolyte is prepared from the following raw materials in weight percentage: 30-35% of ethylene carbonate, 27.5-30% of ethyl methyl carbonate, 5-10% of propylene carbonate, 25-30% of diethyl carbonate and 2.5-5% of vinylene carbonate.

8. The high temperature resistant lithium iron phosphate power battery according to claim 1, characterized in that: The thickness of the coating is 5-8 μm.

9. A process for preparing a high temperature resistant lithium iron phosphate power battery according to any one of claims 1 to 8, characterized in that: The following steps are involved: The carbon-coated lithium iron phosphate, the conductive agent and the binder are mixed and dispersed to obtain a positive electrode material, the positive electrode material is coated on a positive electrode current collector, dried, and cut to obtain a positive electrode sheet; Mixing and dispersing artificial graphite, a conductive agent and a binder to obtain a negative electrode material, coating the negative electrode material on a negative electrode current collector, drying, and cutting to obtain a negative electrode sheet; The positive electrode sheet, the separator and the negative electrode sheet are stacked to obtain a battery cell; The battery cell is assembled into a shell, and the electrolyte is injected. The battery cell is then left to stand at a temperature of 45-50°C and subjected to vacuum forming. After vacuum forming, the battery cell is aged and divided into different capacities at a temperature of 45-50°C to obtain a lithium iron phosphate power battery.

10. The process for preparing a high temperature resistant lithium iron phosphate power battery according to claim 9, characterized in that: During the battery cell manufacturing process, a Z-shaped lamination process is used for lamination, and the vacuum degree of the vacuum is -0.05 to -0.1 KPa.